LINGUO-STYLISTIC STRATIFICATION AS IDENTIFICATION OF FEMININITY IN THE NOVELS “SIRANUSH” BY SRBUHI TYUSAB AND “A GIRL’S HEART” BY SIPIL - Hambardzumyan, Naira; Parsadanyan, Siranush (Armenian Folia Anglistika, 2023)
The paper investigates the linguo-stylistic stratifications in the novels of Western Armenian women authors of the second half of the 19th century, in particular, Srbuhi Tyusab’s Siranush (1884) and Sipil’s A Girl’s Heart (1891), as well as their characteristic features and interpenetrations. The study aims to pinpoint those stratifications as a technique of female writing through the study of the linguistic features of the novels under analysis. The problem of the research is to interpret the literary techniques and devices (comparison, metaphor, oxymoron, ellipses, morphological and syntactic means) used in the mentioned works from a new perspective, clearly highlighting the male-female worldviews and world-images in the fictional works of the female authors. The illustrative material was analyzed with an application of linguistic, literary and comparative methods observing the linguo-styistic stratifications as identification of femininity in a single domain. The mentioned novels have so far not been analysed in terms of linguo-stylistic stratification. The study is important and relevant not only from the point of view of interdisciplinarity, but also that of the analysis of women’s issues in Armenological Studies.
Keywords: Srbuhi Tyusab; Sipil; female discourse; intertext; trope; ellipsis; oxymoron